Crescimento e composição corporal de crianças com diabetes mellitus tipo 1 - Paulino, Maria Fernanda Vanti Macedo, 1964- (2006)
Orientadores: Andre Moreno Morcillo, Sofia Helena Valente de Lemos Marini